The Effect of Group Study on The English Learning Achievement of Students In Middle-School 1 Bunobogu - Kadir, Indri Indarti; Fatmasari, Elly; Iskandar, Iskandar (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The learning process and student learning outcomes have a very close relationship. A good learning process can improve student learning outcomes. Teachers' implementation of the learning process largely determines the improvement of student learning outcomes. Talking about the learning process is the same as talking about learning and teaching methods. When studying, it's crucial to select the appropriate method, as it allows one to utilize all available time effectively and efficiently, thereby facilitating the successful execution of every effort towards the desired goal. This paper focuses on group learning as a learning method, examining its benefits in enhancing English learning outcomes for class VII students at Middle-School 1 Bunobogu. The study draws insights from several relevant literature pieces. discussion, using qualitative descriptive analysis. Therefore, well-planned and implemented group learning can significantly improve learning outcomes and student achievement, making it easier for students to achieve good and satisfying outcomes.